2021
DOI: 10.1002/cctc.202100277
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite‐Supported Rhenium Catalysts for the Deoxydehydration of 1,2‐Hexanediol to 1‐Hexene

Abstract: For the first time ammonium perrhenate (APR) supported on zeolites of the types H-β, H-ZSM-5 and HÀ Y were shown to be efficient catalysts for the deoxydehydration (DODH). They catalyzed the transformation of 1,2-hexanediol (1,2-HDO) to 1hexene in the presence of 3-octanol as reductant and solvent with productivities up to 0.24 mol 1-hexene • g Re À 1 • h À 1 . The productivity decreased with increasing Si : Al ratio, independent of the zeolite structure. Catalyst characterization indicates Re-species to prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The activity and turnover number (TON) of ReO x ‐Pd/CeO 2 were much higher than those of the homogeneous Re catalyst systems, which also supported the heterogeneous catalysis [40] . On the other hand, solid Re catalysts on other supports have been reported to have comparable activity to homogeneous catalysts, and the involvement of leached species in the catalysis cannot be excluded [33,53] . We next developed ReO x ‐Au/CeO 2 catalysts for DODH [54–57] .…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…The activity and turnover number (TON) of ReO x ‐Pd/CeO 2 were much higher than those of the homogeneous Re catalyst systems, which also supported the heterogeneous catalysis [40] . On the other hand, solid Re catalysts on other supports have been reported to have comparable activity to homogeneous catalysts, and the involvement of leached species in the catalysis cannot be excluded [33,53] . We next developed ReO x ‐Au/CeO 2 catalysts for DODH [54–57] .…”
Section: Introductionmentioning
confidence: 72%
“…Most reported DODH systems use homogeneous high‐valent Re catalysts such as CH 3 ReO 3 , ReO 4 − , and monomeric Re VII complexes [26] . The systems in earlier works employ expensive reductants such as PPh 3 , [27,28] and recently reported systems typically use less‐expensive secondary alcohols such as 3‐octanol and 2‐propanol [26,29–34] . However, even secondary alcohols have high price and low atom efficiency as reductants, and their application to the production of bulk chemicals is difficult [20] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, examples of heterogeneous catalysts for DODH are limited, since the Re species can be relatively easily leached from the solid surface and the leached species may participate in the reaction. [16][17][18] The first stable heterogeneous catalyst ReO x /TiO 2 was reported by Palkovits et al 19 for the conversion of 1,2-hexanediol to 1-hexene using 3-octanol as a reductant. Later, Kon et al reported ReO x /γ-Al 2 O 3 as a leaching-free solid DODH catalyst for glycerol conversion to allyl alcohol using 2-hexanol as a reductant.…”
Section: Introductionmentioning
confidence: 99%